ผลของการฝึกสติฐานการสุขศึกษาต่อพฤติกรรมการสร้างเสริมสุขภาพของผู้ป่วย โรคความดันโลหิตสูง ในบริบทศูนย์บริการสุขภาพปฐมภูมิของไทย: วิจัยเชิงคุณภาพ Mindfulness-based Health Education on The Prevention and Promotion Health Behaviors among Hypertensive Patients in A Primary Health Care Unit: A Qualitative Research - แสงประเสริฐ, พานทิพย์; พลังฤทธิ์, ศรีเมือง (วารสารการพยาบาลและการดูแลสุขภาพ, 2019)
Mindfulness is a state of mind, not forgetting from intension, attention and thought inner self attitude process the present moment by moment. Mental activity is inducing awareness and acceptance the conscious and experience that arrive mentally that contributed to control in self-management and promoted self-efficacy in health behavior on hypertensive patients. This qualitative research designed to describe the effects of mindfulness-based health education (MBHE) on prevention and promotion behaviors modifying among state I hypertensive patients at primary healthcare unit. The focus group discussion used to collect data after participation in exercises for 6 weeks. Result showed that improved promoting behaviors in food consumption, motion in exercise, and mental management from physical and mental symptom observing related to induce health promotion and goals of health in daily life, Alert in moment time contributed awareness and acceptance of everything. As a result was a relaxing, deep sleep better and was moody decreasing. Furthermore, physical is blood pressure, heart rate and respiratory rates was decreasing. Conclusion and suggestion, Physical and mental promotion increased from health behavior modification from mindfulness-based health education. These should be adding in the counterpart of health education in promoting hypertensive patients on primary health care unit.